The Commonwealth of Cricket : A Long Love Affair with the Most Subtle and Sophisticated Game Known to Humankind - Guha, Ramachandra (Noida : Harper Collins, 2020)
When Ramachandra Guha began following the game in the early 1960s, India was utterly marginal to the world of cricket: the country still hadn't won a Test match overseas; by the time he joined the Board of Control for Cricket in India, fifty years later, India had become world cricket's sole superpower. The Commonwealth of Cricket is a first-person account of this astonishing transformation. The book traces the entire arc of cricket in India, across all levels at which the game is played: school, college, club, state, country. It presents vivid portraits of local heroes, provincial icons, and international stars. Cast as a work of literature, The Commonwealth of Cricket is keenly informed by the author's scholarly training, the stories and sketches narrated against a wider canvas of social and historical change. The book blends memoir, anecdote, reportage and political critique, providing a rich, insightful and rivetingly readable account of this greatest of games as played in the country that has most energetically made this sport its own.
Keywords: Sports and Leisure -- Nonfiction